2009
DOI: 10.1128/aac.00404-09
|View full text |Cite
|
Sign up to set email alerts
|

Imidocarb Dipropionate Clears PersistentBabesia caballiInfection with Elimination of Transmission Potential

Abstract: Antimicrobial treatment of persistent infection to eliminate transmission risk represents a specific challenge requiring compelling evidence of complete pathogen clearance. The limited repertoire of antimicrobial agents targeted at protozoal parasites magnifies this challenge. Using Babesia caballi as both a model and a specific apicomplexan pathogen for which evidence of the elimination of transmission risk is required for international animal movement, we tested whether a high-dose regimen of imidocarb dipro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
46
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 28 publications
2
46
0
1
Order By: Relevance
“…Treatment results revealed that early intervention using imidocarb dipropionatein in conjunction with supportive treatments as phosphorous and vitamin B12 and two liters of 10% dextrose saline was highly efficient. Similar results were obtained previously by Bruning (1996), de Wall (1990, Friedhoff and Soule (1996) and Schwint et al (2009). Forty percent of the treated horses showed side effects in the form of salivation, colic and sometimes recumbence.…”
Section: Discussionsupporting
confidence: 79%
“…Treatment results revealed that early intervention using imidocarb dipropionatein in conjunction with supportive treatments as phosphorous and vitamin B12 and two liters of 10% dextrose saline was highly efficient. Similar results were obtained previously by Bruning (1996), de Wall (1990, Friedhoff and Soule (1996) and Schwint et al (2009). Forty percent of the treated horses showed side effects in the form of salivation, colic and sometimes recumbence.…”
Section: Discussionsupporting
confidence: 79%
“…The observation that none of the recipient horses became infected with B. caballi suggests that the U.S. horses were not infected with a B. caballi-divergent isolate. Importantly, our previous study demonstrated that blood from carrier horses with B. caballi successfully infected naive seronegative recipient horses via blood transfusion (6).…”
Section: Discussionmentioning
confidence: 99%
“…The restriction of movement is based on the identification of infected animals by direct and indirect methods (5,6). However, several diagnostic assays have failed to detect all infected animals due to a lack of sensitivity in the diagnostic tests, pathogen mutation or recombination, or deficiencies in host immunity (6,23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations